Natural convection of nanofluid inside a wavy cavity with a non-uniform heating Entropy generation analysis - Sheremet, Mikhail; Pop, Ioan; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Emerald Group Publishing Ltd, 2017)
Purpose - The main purpose of this numerical study is to study on entropy generation in natural convection of nanofluid in a wavy cavity using a single-phase nanofluid model. Design/methodology/approach - The cavity is heated non-uniformly from the wavy wall and cooled from the right side while it is insulated from the horizontal walls. The physical domain of the problem is transformed into a rectangular geometry in the computational domain using an algebraic coordinate transformation by introducing new independent variables xi and eta. The governing dimensionless partial differential equations with corresponding initially and boundary conditions were numerically solved by the finite difference method of the second-order accuracy. The governing parameters are Rayleigh number (Ra = 1000-100000), Prandtl number (Pr = 6.82), solid volume fraction parameter of nanoparticles (phi = 0.0-0.05), aspect ratio parameter (A = 1), undulation number (kappa = 1-3), wavy contraction ratio (b = 0.1-0.3) and dimensionless time (tau = 0-0.27). Findings - It is found that the average Bejan number is an increasing function of nanoparticle volume fraction and a decreasing function of the Rayleigh number, undulation number and wavy contraction ratio. Also, an insertion of nanoparticles leads to an attenuation of convective flow and enhancement of heat transfer. Originality - The originality of this work is to analyze the entropy generation in natural convection within a wavy nanofluid cavity using single-phase nanofluid model. The results would benefit scientists and engineers to become familiar with the flow behaviour of such nanofluids, and will be a way to predict the properties of this flow for the possibility of using nanofluids in advanced nuclear systems, in industrial sectors including transportation, power generation, chemical sectors, ventilation, airconditioning, etc.
Keywords: Nanofluid; Entropy generation; Numerical results; Natural convection; Wavy cavity; Non-uniform heating